Long-Term Mortality after Pneumonia - Mortensen, Eric M.; Metersky, Mark L. (Seminars in Respiratory and Critical Care Medicine, 2012)
Although pneumonia is currently considered the eighth leading cause of death in the United States this estimate includes only short-term mortality. Evidence suggests that pneumonia may have significant longer-term effects and that hospitalization for pneumonia is associated with higher long-term mortality than for many other major medical conditions. Reasons for this increased mortality appear to be due to several factors, including cardiovascular disease, neoplasms, and alterations in immune function. Clinicians need to be aware that even for those patients who survive the initial episode of pneumonia there will still be an impact upon their potential survival for the coming years.
Keywords: community-acquired pneumonia; mortality; prognosis; long-term effects; pneumonia; long-term mortality